Genome sequences of two diploid wild relatives of cultivated sweetpotato reveal targets for genetic improvement - Shan Wu (Nature Portfolio, 2018)
Sweetpotato is an important food security crop providing rich source of macro- and micronutrients including carbohydrates and vitamins. Here, the authors assemble of the two diploid relatives of cultivated sweetpotato and identify genes and alleles associated with carotenoid biosynthesis from breeding lines.